Penerapan Model Pembelajaran Project Based Learning untuk Meningkatkan Keterampilan Berpikir Kreatip Siswa Kelas IV Sekolah Dasar Negeri 069/VI Talang Tembago - Arlin Pratama Putra; Andi Nurhasanah (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2025)
One of the skills that must be possessed by Indonesian people in facing the 21st century is the ability to think creatively. Because creative thinking is part of life skills that need to be developed in facing the information era and increasingly competitive atmosphere. But unfortunately creative thinking skills are still relatively low in Class IV of SD N 69 VI Talang Tembago. The Project Based Learning learning model is used as a solution to improve students' creative thinking skills because the learning model focuses on characteristics and principles that aim for students to be actively involved in learning, in producing a project or work based on the results of creative thinking. The research method used in this study is the Classroom Action Research Method (CAR), This study uses the Jhon Elliot Model which consists of four stages. The purpose of this study is to improve the creative thinking skills of class IV students of Sd N 69 / VI Talang Tembago. Based on the results of observations of teacher activities in cycle I, the results were obtained with a percentage of 58% sufficient qualifications, then in cycle II teacher activities increased to 87% very good qualifications. Meanwhile, the results of observations of student activities in cycle I obtained results of 60% and increased in cycle II to 80% with good qualifications. Based on these data, it shows an increase in teacher and student activity in the application of the Project Based Learning Model in the learning process. Thus, it can be concluded that the application of the Project Based Learning Model is able to improve the creative thinking skills of students in grade IV of Sd N 69/VI Talang Tembago.